2015
DOI: 10.1007/s12011-015-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

New Evidences of Key Factors Involved in “Silent Stones” Etiopathogenesis and Trace Elements: Microscopic, Spectroscopic, and Biochemical Approach

Abstract: The knowledge of the key factors involved in etiopathogenesis of the gallstone disease requires chemical, structural, and elemental composition analysis. The application of different complementary analytical techniques, both microscopic and spectroscopic, are aimed to provide a more comprehensive determination of the gallbladder calculi ultrastructure and trace element identification. High sensitivity techniques such as electron microscopy (SEM), Fourier transform infrared (FTIR), electron paramagnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Gallstones are classified into cholesterol stones, brown stones, black stones, and mixed stones [79]. The white stones are composed of ≥50% of cholesterol, whereas black and brown stones, which contain different proportions of cholesterol and bilirubin, are composed of ≤30% of cholesterol by weight [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstones are classified into cholesterol stones, brown stones, black stones, and mixed stones [79]. The white stones are composed of ≥50% of cholesterol, whereas black and brown stones, which contain different proportions of cholesterol and bilirubin, are composed of ≤30% of cholesterol by weight [10].…”
Section: Discussionmentioning
confidence: 99%
“…The white stones are composed of ≥50% of cholesterol, whereas black and brown stones, which contain different proportions of cholesterol and bilirubin, are composed of ≤30% of cholesterol by weight [10]. Gallstone components other than cholesterol and bilirubin include calcium carbonate, phosphate salts, phospholipids, fatty salts, polysaccharide, and proteins, along with minor elements such as potassium, calcium, manganese, iron, copper, zinc, chlorine, and sulfur [7, 1114]. In the present patient, infrared spectroscopy revealed that the bezoar was composed of fatty acid calcium, calcium carbonate, and bilirubin calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from literature abounds with information on the pronucleating factors in bile, such as N‐aminopeptidase, fibronectin, immunoglobulins, acidic glycoproteins, mucin, and lipoproteins . Cavalu et al , using a deconvolution procedure, report that the random coils may represent the dominant secondary structure of proteins that may be involved in GS pathogenesis. The XRD pattern in their study confirmed that mixed and pigment GS had calcium bilirubinate complex formation, together with anhydrous and monohydrate forms of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The amide I spectral band was baseline-corrected, and the area was normalized and deconvoluted in the interval 1600-1700 cm −1 . The percentage of protein secondary structures (α-helix, β-sheets, turns, unordered and side chains) was calculated based on the area under each peak, and the assignments of the components were conducted according to the literature [19][20][21]. Results were represented as mean ± standard deviation (SD) for three independent experiments.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…In the higher-wavenumber region, the interval 3190-3300 cm −1 is assigned to O-H and C-H bending vibrations, while the band at 2950 cm −1 can be assigned to the asymmetric stretching mode of the CH3 group. The O-H stretching region can be correlated to the hydrogen bond network around the protein, assuming that a certain hydration level still exists after the drying procedure [19,24]. However, water deprivation and restitution might have some consequences on the macromolecular structure.…”
Section: Ftir Spectroscopymentioning
confidence: 99%